Infection of Gastro-intestinal Parasites in Native Chicken (Gallus domesticus) in Sub-district of Kupang Tengah, Kupang Regency - Seran, Hildegardis Hoar; Almet, Julianty; Raja Mangihut Ronael Simata, Yohanes Timbun; Lestari. Djungu, Dewi Fesbayati; Winarso, Aji (Jurnal Medika Veterinaria, 2024)
Rural communities in Kupang Regency generally raise native chickens as an additional income. The rearing of native chickens in Kupang Regency is still mostly in the form of extensive farming, making them vulnerable to parasitic infections. Parasitic infections in native chickens lead to decreased productivity. This study aimed to determine the prevalence and degree of gastro-intestinal parasite infection in native chicken (Gallus domesticus) in Sub-district of Kupang Tengah, Kupang Regency. A total amount of 56 fecal samples were collected from native chicken in 4 villages. Fecal samples were examined using the McMaster and sedimentation methods. This research found 5 types of endoparasites that infect native chickens in Sub-district of Kupang Tengah, namely: Ascaridia galli, Heterakis gallinarum, Trichuris sp, Railletina sp. and parasitic Protozoa (Eimeria spp). The degree of endoparasite infection in chickens in Central Kupang District was: Nematodes (Ascaridia galli and Heterakis gallinarum) were categorized as moderate infection, and Trichuris sp was included in the category of mild and severe infection. While in the class of Cestoda (Railletina sp) and Protozoa (Eimeria sp) were included in the category of mild infection